Gloss to the judgment of the Supreme Court of 26 January 2022, IV KK 666/21 - Chrabkowski, Marek (Studia Iuridica Toruniensia, 2023)
The critical gloss to the judgment of the Supreme Court, which in the justification of its ruling expressed the view that the condition after using an agent similar to alcohol is tantamount to the presence of this agent in the body. The author of the gloss was also critical of the thesis that the use of a narcotic drug does not mean that the narcotic drug has a real impact on the psychomotor skills of the driver.